1998
DOI: 10.1271/bbb.62.532
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Acetyl-CoA Carboxylase Inhibitors from Green Tea (Camellia sinensis).

Abstract: An aqueous methanol extract from green tea showed potent acetyl-CoA carboxylase inhibitory activity. An active compound was isolated from the extract and identified as (-)-epigallocatechin gallate by instrumental analyses. The IC50 value of (-)-epigallocatechin gallate was 3.1 x 10(-4) M. Among tea catechins and related compounds, nearly equal activity was found in (-)-epigallocatechin gallate and (-)-epicatechin gallate, whereas (+)-catechin, (-)-epicatechin, (-)-epigallocatechin, gallic acid and methyl galla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 14 publications
2
77
0
1
Order By: Relevance
“…Sayama et al, reported that the addition of green tea powder (GTP) to the diet suppressed fat accumulation and body weight increase without reduction of food intake in mice [17]. Moreover, it was reported that epigallocatechin gallate (EGCG), a kind of catechin, had an inhibitory effect on acetylCoA carboxylase which is essential for in vitro fatty acid biosynthesis [18]. Weight loss (one of the clinical features of diabetes) seen in alloxan-treated animals may be due to the degeneration of the adipocytes and muscle tissues to compensate for the energy lost from the body due to frequent urination and overconversion of glycogen to glucose [19].…”
Section: Results and Discussion Changes In Body Weightmentioning
confidence: 99%
“…Sayama et al, reported that the addition of green tea powder (GTP) to the diet suppressed fat accumulation and body weight increase without reduction of food intake in mice [17]. Moreover, it was reported that epigallocatechin gallate (EGCG), a kind of catechin, had an inhibitory effect on acetylCoA carboxylase which is essential for in vitro fatty acid biosynthesis [18]. Weight loss (one of the clinical features of diabetes) seen in alloxan-treated animals may be due to the degeneration of the adipocytes and muscle tissues to compensate for the energy lost from the body due to frequent urination and overconversion of glycogen to glucose [19].…”
Section: Results and Discussion Changes In Body Weightmentioning
confidence: 99%
“…ACC is the rate-limiting step in fatty acid synthesis for catalyzing the conversion of acetyl-CoA to malonyl-CoA (the precursor of fatty acids). When green tea ECG or EGCG was incubated with rat liver ACC, both catechins (with a Ki of 310 lM) inhibited the activity of ACC [63]. However, neither (+)-catechin, EC, nor EGC has that effect.…”
Section: Inhibition Of Lipogenic Enzymesmentioning
confidence: 96%
“…8) Each sample was assayed for SOD activity by using a colorimetric SOD assay kit (Dojindo Molecular Tec.). The absorbance was measured at 450 nm with a plate reader to determine the percentage SOD activity as ½ðA blank 1 À A blank 3 Þ À ðA sample À A blank 2 Þ=ðA blank 1 À A blank 3 Þ Â 100%.…”
Section: Methodsmentioning
confidence: 99%